Arduino-powered real-time library seating availability system - Megat Haris Nasution, Putri Nabilah; Ahmad Haniff, Nur Adira Aqila; Sahrani, Muhammad Emir Ismail; Rahimi, Safwatunnisa (Universiti Teknologi Mara, Kedah, 2023)
The challenge of locating available study seats in contemporary libraries is exacerbated by limited seating and an unfamiliar layout, especially in large, multi-story libraries. This issue is particularly pronounced during examination periods when libraries are densely populated, making it difficult for students and visitors to find suitable study spaces efficiently. To address this problem, we propose a Library Seat Availability Live Monitoring System using Arduino technology. Our system integrates an Arduino UNO, infrared (IR) sensors, and an LCD to create a real-time monitoring mechanism for seat availability. The IR sensors adeptly detect motion and body heat within the seating area, transmitting signals to the Arduino UNO, which processes the data and presents the count of available seats on an LCD screen. This strategic deployment of sensor networks enables users to swiftly identify unoccupied study spots, eliminating the need for extensive exploration within the library. The lab-scale prototype of our system will be evaluated for its accuracy and time efficiency in detecting available seats. The results will provide insights into the feasibility and practicality of implementing such a solution on a larger scale within library environments. Furthermore, this work sets the foundation for future enhancements, including developing web and mobile apps. These applications could allow users to navigate the library layout, identify available seats, and reserve online study spots. By integrating technology into the library experience, we aim to streamline the process of finding and securing study spaces, saving visitors valuable time and enhancing the overall efficiency of library resource utilization.